DAMPAK PENGGUNAAN GAWAI TERHADAP HASIL BELAJAR MAHASISWA IKIP SILIWANGI BANDUNG - Anis Amalia; Asri Anggraeni Rahayu Rachman; Sinta Nuri Handayani; Yeni Rostikawati (IKIP Siliwangi, 2018)
The use of gadget in society currently cannot be separated in daily live activity, especially for students. This electronic gadget gives and provides specific information that we need. Surely, this make student’s ease to find matter about any subjects. The purpose of this research is to know how far is the effect to students of IKIP Siliwangi Bandung about their study result. This research is a descriptive qualitative research, so the effect of gadget to IKIP Siliwangi Bandung students are shown completely and detailed. The Instrument to take data was using online questionnaire that was distributed to whole IKIP Siliwangi Bandung students, with 41 respondents that fulfill five aspect on the questionnaire, use Guttmann scale to analyze the data. From 41 respondent the results are; commonly gadget effect to students about 48,53%, study by gadget about 55,12%, study without gadget about 35,7%, the effect of gadget about their study result about 46,34%, and the effect of study without gadget about 46,95%. The result shown that gadget is giving effect about the way students study, but is not effecting the result of study.